Simplify the Expression: 5³ × 2⁴ × 5² × 2³ Using Laws of Exponents

Question

Simplify the following equation:

53×24×52×23= 5^3\times2^4\times5^2\times2^3=

Video Solution

Solution Steps

00:00 Simply
00:03 Let's arrange the exercise so that equal bases are adjacent
00:16 According to laws of exponents, when multiplying powers with the same base (A)
00:21 We get the same base (A) raised to the sum of exponents (M+N)
00:25 Let's use this formula in our exercise
00:29 Let's compare terms according to the formula and simplify
00:35 Let's keep the base
00:40 Let's sum the exponents
01:00 Let's use the same method to simplify the second base
01:21 And this is the solution to the question

Step-by-Step Solution

Let's simplify the expression 53×24×52×23 5^3 \times 2^4 \times 5^2 \times 2^3 using the rules for exponents. We'll apply the product of powers rule, which states that when multiplying like bases, you can add the exponents.

  • Step 1: Focus on terms with the same base.
    Combine 53 5^3 and 52 5^2 . Since both terms have the base 55, we apply the rule am×an=am+na^m \times a^n = a^{m+n}: 53×52=53+2=55 5^3 \times 5^2 = 5^{3+2} = 5^5

  • Step 2: Combine 24 2^4 and 23 2^3 . Similarly, for the base 22: 24×23=24+3=27 2^4 \times 2^3 = 2^{4+3} = 2^7

After simplification, the expression becomes:
55×27 5^5 \times 2^7

Answer

55×27 5^5\times2^7